2009
DOI: 10.1037/a0017498
|View full text |Cite
|
Sign up to set email alerts
|

Core self-evaluations and job performance: The role of the perceived work environment.

Abstract: Using trait activation theory as a framework, the authors examined the moderating role of two situational variables-perceptions of organizational politics and perceptions of leader effectiveness-on the relationship between core self-evaluations and job performance. Results from two samples (N = 137 and N = 226) indicate that employee perceptions of their work environment moderated the relationship between their core self-evaluations and supervisor ratings of their performance. In particular, those with higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
133
0
7

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 178 publications
(151 citation statements)
references
References 70 publications
11
133
0
7
Order By: Relevance
“…Collins, Harris and Judge (2009) found that CSE strengthened the effect of perceptions of leader effectiveness on performance. Research has also demonstrated that CSE shields against the effects of negative work-place phenomena (e.g., Greenbaum, Mawrtiz and Elissa, 2012;McNall, Masuda, Rhoades Shanock, and Nicklin, 2011;Ritz, Shantz, Alfes, and Arshoff, 2012).…”
Section: Core Self-evaluations and Self-verification Theorymentioning
confidence: 99%
“…Collins, Harris and Judge (2009) found that CSE strengthened the effect of perceptions of leader effectiveness on performance. Research has also demonstrated that CSE shields against the effects of negative work-place phenomena (e.g., Greenbaum, Mawrtiz and Elissa, 2012;McNall, Masuda, Rhoades Shanock, and Nicklin, 2011;Ritz, Shantz, Alfes, and Arshoff, 2012).…”
Section: Core Self-evaluations and Self-verification Theorymentioning
confidence: 99%
“…Employees who are placed higher in evaluating themselves positively will be more persevering and motivated at the workplace and are found highly confident in their actions, powers and capabilities and have belief in their abilities and considered themselves as likely to be more succeeded, and this faith in themselves enhances the performance levels of such individuals and decrease their intent to leave that place (Judge, Locke et al, 1998). Research in this regard has indicated that the individuals with a high internal locus of control when given with the negative feedback tends to improve or increase their performance to remove the discrepancies between actual and standard performance (Kacmar, Collins, Harris & Judge, 2009). While, individuals having low self-esteem uses their negative feedback by either decreasing their standards of performance or by completely getting withdrawal from the task or in the face of increase in turnover intentions (Kacmar et al, 2009).…”
Section: Core Self Evaluation and Turnover Intentionsmentioning
confidence: 99%
“…However, subsequent research with personality characteristics has shown that it has a significant effect on POP and these personal characteristics have basically more contribution in POP than one's demographic variables (Kacmar et al, 2009). So generally one's personality traits are considered to be more important in POP because it determines their behavior and perception towards organizational politics (Kacmar et al, 2009). A person having an external locus of control thinks that his destiny is out of his control and dependent on environmental factors, while the persons with high internal locus of control have a belief that they have a strong command on their lives.…”
Section: Moderating Effect Of Cse On Pop and Turnover Intentionsmentioning
confidence: 99%
See 2 more Smart Citations